Perbandingan Penerapan Pidana Mati Dalam Hukum Pidana Indonesia Dan Tiongkok Dengan Studi Tindak Pidana Korupsi - Nurcahyani, Dewita; Adliya, Clarissa Dewi; Susanto, Muhamad Farel Putra (Universitas Pahlawan Tuanku Tambusai, 2025)
The young Chinese generation in Indonesia currently faces significant challenges in maintaining an understanding and appreciation of their cultural heritage. Factors such as globalization, urbanization, and rapid lifestyle changes have introduced new values that often conflict with Chinese traditions. Additionally, the policies of the New Order regime, which restricted Chinese cultural practices, have contributed to the younger generation's difficulty in understanding their cultural legacy. This study aims to identify the causes of declining cultural understanding among young Chinese Indonesians and to explore the roles of family, community, and education in preserving these traditions and values. A mixed-method approach is used in this research, combining quantitative methods through surveys and qualitative methods through observations and in-depth interviews within communities, schools, and family environments. The results of this study are expected to provide practical solutions to enhance young Chinese Indonesians' understanding and appreciation of their cultural heritage, including through the development of accessible learning resources at home, in schools, and within communities.